Clinical value of CA125, AFP, and CEA for combined diagnosis and assessment of gastric cancer prognosis - Yanhai Jia; Yajuan Wang; Haiying Li; Yamei Yang; Min Sun (Frontiers in Oncology)
To analyze the diagnostic and prognostic value of combined detection of CA125, AFP, and CEA for gastric cancer. Ninety-eight gastric cancer patients treated in our hospital from January 2020 to November 2022 were retrospectively selected and classified into the gastric cancer group according to screening criteria, while 80 patients diagnosed with benign gastric lesions during the same period were classified into the benign group. Serum levels of CA125, AFP, CEA, and their positive rates were significantly higher in the gastric cancer group compared to the benign group (P<0.05). The AUCs for CA125, AFP, CEA, and their combined detection in diagnosing gastric cancer were 0.815, 0.813, 0.911, and 0.919, respectively (P<0.001). In patients with stage III-IV, the levels of CA125, AFP, and CEA were higher than those in stage I-II (P<0.05). The AUCs for serum CA125, AFP, CEA, and their combined detection in TNM staging of gastric cancer were 0.751, 0.834, 0.911, and 0.931, respectively (P<0.001). Poorly differentiated patients had higher levels of CA125, AFP, and CEA compared to moderately to well-differentiated patients (P<0.05). The AUCs for serum CA125, AFP, CEA, and their combined detection in diagnosing differentiation degree were 0.819, 0.883, 0.746, and 0.986, respectively (P<0.001). Patients with metastasis had higher levels of CA125, AFP, and CEA compared to those without metastasis (P<0.05). The AUCs for serum CA125, AFP, CEA, and their combined detection in diagnosing metastasis were 0.716, 0.825, 0.863, and 0.892, respectively (P<0.001). The levels of CA125, AFP, and CEA of patients in the death group were higher than those in the survival group (P<0.05). The AUCs for serum CA125, AFP, CEA, and their combined detection in predicting clinical outcomes of gastric cancer patients were 0.713, 0.809, 0.922, and 0.926, respectively (P<0.001). Cox regression analysis indicated that TNM staging, peritoneal metastasis, and elevated CEA levels were independent risk factors for poor prognosis (mortality) in patients with gastric cancer (P<0.05). Serum levels of CA125, AFP, and CEA in patients with gastric cancer were significantly elevated and were correlated with the degree of differentiation and TNM staging. Combined detection had diagnostic efficacy in assessing metastasis and clinical outcomes.